(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
The objective of this paper is to determine how winemakers in Eastern Continental Croatia use marketing in their business. In addition, the paper aims to analyse the distribution of wine products and identify promotional activities that are considered most appropriate for the promotion of wine and further development of the wine sector. A survey was the method used to collect the data, and a survey questionnaire was used as the instrument. The survey was performed on a sample of n=30 winemakers from five counties in Eastern Croatia (Osijek-Baranja, Vukovar-Srijem, Virovitica-Podravina, Požega-Slavonija, and Brod-Posavina). The surveyed winemakers use a combination of direct and indirect distribution channels to sell their wine. The majority of surveyed winemakers sell wine through channels such as the cellar door and wine festivals. These channels are particularly attractive to small and medium winemakers because they can increase their profits. However, to be competitive in the market, Croatian winemakers must adopt new distribution channels and means of communication, increase their marketing efforts and make a shift from sales-oriented to market-oriented strategy.